2014
DOI: 10.7567/jjap.53.07kg02
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of convolution and Reed–Solomon codes in underwater multipath fading channel

Abstract: In underwater acoustic communication, the transmitted signal is affected by multipath fading and background noise. Therefore, the intersymbol interference (ISI) of underwater acoustic communication systems depends on the effects of these parameters. To cope with ISI due to multipath fading, various equalizers and orthogonal frequency division multiplexing systems have been developed. Forward error correction coding is also adopted to reduce the error by background noise. Here, the performances of convolution c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…We have developed ET-01, a phosphorescent host material with a dibenzoquinoxaline electron-transport skeleton [5], and RD-01, a deep-red phosphorescent dopant iridium (Ir) complex with a phenylpyrazine ring ligand [3]. A top-emission device containing ET-01 and RD-01 in an EmL satisfied the red chromaticity of the BT.2020 standard and had an LT 95 of ~600 h with a driving current density of 10 mA/cm 2 and an initial luminance of ~1500 cd/m 2 at RT [3].…”
Section: Characteristics Of Our Extet Devicementioning
confidence: 99%
See 1 more Smart Citation
“…We have developed ET-01, a phosphorescent host material with a dibenzoquinoxaline electron-transport skeleton [5], and RD-01, a deep-red phosphorescent dopant iridium (Ir) complex with a phenylpyrazine ring ligand [3]. A top-emission device containing ET-01 and RD-01 in an EmL satisfied the red chromaticity of the BT.2020 standard and had an LT 95 of ~600 h with a driving current density of 10 mA/cm 2 and an initial luminance of ~1500 cd/m 2 at RT [3].…”
Section: Characteristics Of Our Extet Devicementioning
confidence: 99%
“…In the EmLs, ET-01 and ET-02 each forms an exciplex together with the assist material, and excited energy is transferred from the exciplex to the guest material. Such an energy transfer process is referred to as exciplex-triplet energy transfer (ExTET) [5][6][7][8][9]. The ExTET contributes to high efficiency and low driving voltage.…”
Section: Characteristics Of Our Extet Devicementioning
confidence: 99%
“…RGR Emission Unit achieved high efficiency and low drive voltage using phosphorescent-layer emission enhanced by energy transfer from an exciplex to a dopant. We call this technique exciplex triplet energy transfer (ExTET) [17][18][19][20][21]. These technologies we newly developed are essential for high efficiency and long lifetime in the white tandem OLED.…”
Section: B/rgr Tandemmentioning
confidence: 99%
“…Using as host two types of material with different carrier transport properties allows facile adjustment of the carrier balance in the light-emitting layer (EmL). Additionally, in the previous work, we found that an exciplex formed by the two hosts, plays an important role in increasing the efficiency and lifetime of an OLED [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%